Promoting Universal Health Coverage and Decent Work: Mainstreaming SDGs at the 42nd ASEAN Summit in 2023 - Larassita Damayanti; Yanuar Nugroho; Yulia Rimapradesi (UNIDA Gontor, 2026)
The issue of Universal Health Coverage (UHC) and decent work remains vital to ensure social and economic growth. As a region with diverse backgrounds like ASEAN, this is quite challenging. In fact, UHC and decent work are strategic issues to achieve ASEAN Charter and the 2030 SDGs target. However, challenges remain still after 17 years of ASEAN Charter’s enforcement and 10 years of SDGs’ adoption. This research applies a qualitative approach with the focus on ASEAN integration and strategic preference. As for the scope of analysis, it will limit only on the 42nd ASEAN Summit 2023. Result confirms that ASEAN’s leaders commit to strengthen UHC. However, there was no declaration on decent work, since the focus is on protecting migrant workers and their relative. As for the SDGs, they are mainstream in ASEAN’s agendas. To sum up, UHC and SDGs become key issues during the summit, but not for decent work.